Inventarisasi Makanan Dan Minuman Tradisional Di Desa Satra Kecamatan Kintamani - I Made Purwa Dana Atmaja (JURNAL GASTRONOMI INDONESIA, 2022)
This study aims to compile a detailed inventory of traditional Balinese food in Satra Village, Kintamani District which includes: (a) main meals, (b) side dishes made from vegetable and animal ingredients, (c) snacks or snacks, (d) drinks and (e) regional specialties. This type of research is survey research with descriptive method. Methods of collecting data were interviews, participatory observation, and documentation methods. Furthermore, the data were analyzed descriptively qualitatively, namely exposure with words to describe the object under study. The depiction of research data is carried out objectively according to the actual situation. Based on the results of interviews, observations and documentation, it was found that traditional Balinese food in Satra Village can be grouped into five groups, namely consisting of 3 types of main food, 8 types of side dishes from vegetable ingredients and 4 types of animal foods, snacks or snacks totaling 7 types, 5 types of drinks and 5 types of special foods